How to be rich: collected wisdom from the world's greatest thinkers / edited by Patricia G. Horn - "Horan, Patrica G. (ed.)" (London, 2007)
Does your life include an abundance of riches and wealth? Are you living up to your full potential; mentally, physically and spiritually? If your answer to these questions is 'no' then How to be Rich can change your situation and inspire you to chart a course to personal wealth, happiness and fulfilment.With choice excerpts from the writings of eleven of the world's great historical leaders in success, such as Napoleon Hill, How to be Rich provides proven wealth-attracting steps and strategies based on one basic idea: the key to everything is our thought. How to be Rich is a refreshing look at our thoughts, desires and actions and how we are moulding the circumstances of our life. Take control of your prosperity and let How to be Rich teach you how to acquire wealth and riches.
Keywords: Riches and wealth